Detecção de genes codificadores de enterotoxinas e resistência aos antimicrobianos fenotípica e genotípica, mecA e vanA e expressão gênica em estafilococos SCP e SCN isolados de mastite bovina - Guimarães, Felipe de Freitas [UNESP] (2015)
A total of 300 isolates of bovine mastitis cases from several Brazilian dairy herds were studied, respectively: 150 CPS and 150 CNS strains. The isolates were analyzed to enterotoxins codifying genes by Polymerase Chain Reaction (PCR). Gene expression was evaluated by reverse transcription PCR (RT-PCR). The isolates were subjected to sensitivity profile correlated with the detection of mecA and vanA gene by PCR. Among the CNS the following species were identified: 48 (32%) S. warneri, 22(15%) S. epidermidis, 20(13%) S. hyicus, 10(7%) S. xylosus, 7(5%) S. haemolyticus, 6(4%) S. simulans, 6(4%) S. schleiferi subsp schleiferi, 6(4%) S. hominis, 5(3%) S. pasteuri, 4(2.7%) S. cohnii, 3(2%) S. saprophyticus subsp. saprophyticus 3(2%) S. chromogenes 3(2%) S. sciuri, 2(1%) S. saccharolyticus, 2(1%) S. lugdunensi, 1(0,7%) S. auriculares, 1(70%) S. saprophyticus subsp. bovis and 1(0.7%) S. capitis. Among the 150 CPS: 105 (70%) S. aureus, 21(14%), S. hyicus, 19(13%), S. intermedius and 5(3%) S. schleiferi subsp coagulans. The identification by phenotypic and genotypic tests showed a concordance of 96.7% in the CNS isolates, and 98.7% in the CPS. The codifying genes to enterotoxins production were detected to classical and enterotoxin-like in 175 (58%) out of 300 staphylococci isolates. These genes were detected significantly higher among the CNS (73%) in relation to CPS (44%), P<0.0001. In 109 CNS codifying genes to enterotoxins were detected in the following species: 37(33.9%) S. warneri, 17(15.6%) S. epidermidis, 16(14.7%) S. hyicus, 5(4.6%) S. xylosus, 5(4.6%) S. haemolyticus, 4(3.7%) S. simulans, 4(3.7%) S. schleiferi subsp schleiferi, 4(3.7%) S. homini, 4(3.7%) S. pasteuri, 3(2.7%) S. saprophyticus subsp. saprophyticus, 3(2.7%) S. cohnii, 3(2.7%) S. chromogenes, 2(1.8%) S. sciuri, 1(0.9%) S. lugdunensis and 1(0.9%) S. capitis. Among the 66 CPS, the enterotoxin genes were observed in the following species: 48(73 %) S. aureus, 10(15%) S. hyicus, ...